Considerations for addressing anti‐vaccination campaigns: How did we get here and what can we do about it? - Jeffrey S. Barrett; Scarlett Y. Yang; Kavitha Muralidharan; Victoria Javes; Kemi Oladuja; María Sofía Castelli; Nicole Clayton; Jiaqi Liu; Andre Ramos (Wiley, 2022)
Abstract A course on vaccine development asked students to write a blog addressing general anti‐vaccination strategies and their significance today, in the context of the resistance seen against novel SARS‐CoV‐2 mRNA vaccines. This perspective explores how and why these efforts are successful at reducing vaccine uptake and why, for the most part, efforts to combat the movement have been unsuccessful. This summary of the collective view of the class provides recommendations for combatting current and future campaigns of misinformation. It is hoped that this perspective will serve as a call to action for clinical pharmacologists and translational scientists to do their part to educate the lay community and promote the science in an open and transparent manner to ensure that current and future vaccines fulfill their potential.